Oxygenation performance assessment of an artificial lung in different central anatomic configurations. Issue 5 (May 2023) - Hima, Flutura; Kalverkamp, Sebastian; Kashefi, Ali; Mottaghy, Khosrow; Zayat, Rachad; Strudthoff, Lasse; Spillner, Jan; Mouzakis, Foivos
Objectives: Aim of this work was to characterize possible central anatomical configurations in which a future artificial lung (AL) could be connected, in terms of oxygenation performance. Methods: Pulmonary and systemic circulations were simulated using a numerical and an in vitro approach. The in vitro simulation was carried out in a mock loop in three phases: (1) normal lung, (2) pulmonary shunt (50% and 100%), and (3) oxygenator support in three anatomical configurations: right atrium-pulmonary artery (RA-PA), pulmonary artery-left atrium (PA-LA), and aorta-left atrium (Ao-LA). The numerical simulation was performed for the oxygenator support phase. The oxygen saturation (SO2 ) of the arterial blood was plotted over time for two percentages of pulmonary shunt and three blood flow rates through the oxygenator. Results: During the pulmonary shunt phase, SO2 reached a steady state value (of 68% for a 50% shunt and of nearly 0% for a 100% shunt) 20 min after the shunt was set. During the oxygenator support phase, physiological values of SO2 were reached for RA-PA and PA-LA, in case of a 50% pulmonary shunt. For the same conditions, Ao-LA could reach a maximum SO2 of nearly 60%. Numerical results were congruous to the in vitro simulation ones. Conclusions: Both in vitro and numerical simulations were able to properly characterize oxygenation properties of a future AL depending on its placement. Different anatomical configurations perform differently in terms of oxygenation. Right to right and right to left connections perform better than left to left ones.